2021
DOI: 10.1111/een.13005
|View full text |Cite
|
Sign up to set email alerts
|

Between locality variations in the seasonal patterns of dung beetles: the role of phenology in mitigating global warming effects

Abstract: 1. Global warming may especially affect ectothermic insect species, making it necessary to forecast the capacity of these species to cope with climatic changes.2. In this study, we use circular statistics to examine the seasonal plasticity of 32 dung beetle species in 17 localities of a mountain Iberian assemblage. We assume that the high variability between localities in the seasonal patterns for the same species suggests that seasonal plasticity could minimise the demographic effects of climate change on loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…In cold temperate regions, the dung beetle activity reaches a peak at early summer (Hanski & Cambefort, 1991). However, in southern Euro-Mediterranean localities, the need to cope with the summer drought generates two main peaks of activity: one in spring and another minor in autumn (Lumaret & Kirk, 1987;Cuesta, Mingarro & Lobo, 2021). Although lifespans of up to 5 years have been recorded, the adults of most small and medium-sized species have a longevity of a few months (Cultid-Medina & Martínez-Quintero, 2019), and one generation in the same year or two in some cases (Martín-Piera & López-Colón, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cold temperate regions, the dung beetle activity reaches a peak at early summer (Hanski & Cambefort, 1991). However, in southern Euro-Mediterranean localities, the need to cope with the summer drought generates two main peaks of activity: one in spring and another minor in autumn (Lumaret & Kirk, 1987;Cuesta, Mingarro & Lobo, 2021). Although lifespans of up to 5 years have been recorded, the adults of most small and medium-sized species have a longevity of a few months (Cultid-Medina & Martínez-Quintero, 2019), and one generation in the same year or two in some cases (Martín-Piera & López-Colón, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal and diel temporal dimensions would be able to interact with each other in dung beetles. Spatial variation in the phenology of dung beetles has been widely observed (Hanski, 1980;Hanski & Cambefort, 1991;Palmer, 1995;Errouissi et al, 2011;Cuesta, Mingarro & Lobo, 2021) as well as inter-annual phenological changes associated with climatic changes (Menéndez & Gutiérrez, 2004;Cuesta & Lobo, 2019). In addition, diel activity can be affected by temperature (Giménez-Gómez et al, 2018), the quantity of trophic resources (Martín-Piera, Sanmartín & Lobo, 1994), and mainly by the seasonality.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys were carried out at the onset of each season, and perhaps, time was not enough to observe a decrease in the abundance of beetles in dry season or an increase in wet season. Since dung beetle species could partially adapt to the effects of climate change by modifying their phenological occurrence (Cuesta et al, 2021), as has been shown by other studies in regions with a well‐defined climate (Andresen, 2005; Cuesta et al, 2021; de Siqueira Neves et al, 2010). In addition, small species may be more abundant in dry season to avoid competition with other dung beetle species (Andresen, 2005).…”
Section: Discussionmentioning
confidence: 80%
“…Thus, the ability of a species to live under colder conditions without spatial modifications of the distribution may require physiological, phenological or diel changes that are difficult to produce. Mediterranean dung beetle species can only partially vary their phenological occurrence to mitigate the effects of climate change (Cuesta et al., 2021). Furthermore, the thermal responses of dung beetle species to different niche dimensions are often unrelated (Calatayud et al., 2021), so fulfilling the temperature requirements for one niche dimension may result in negative effects on other dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the greater sensitivity of Aphodiinae species to environmental conditions favors a spatial response to changes in temperature. This greater sensitivity to environmental changes among Aphodiinae species would also be manifested in their ability to modify their phenology (Cuesta et al., 2021) or the alteration of their populations in response to a decrease in trophic resources (Tonelli et al., 2019). According to our results, the most frequent spatial adaptation strategy is related to an increase in the elevation of the occurrences, although changes due to differences in both latitude and longitude are also frequent.…”
Section: Discussionmentioning
confidence: 99%